2017
DOI: 10.1016/j.gaitpost.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

What can gait tell us about dementia? Review of epidemiological and neuropsychological evidence

Abstract: An integrated approach for evaluating these major geriatric syndromes, based on their close relationship, will not only increase our understanding of cognitive-motor interactions, but most importantly may be used to aid early diagnosis, prognosis and the development of new interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 131 publications
3
68
0
6
Order By: Relevance
“…With regard to the mechanisms linking walking speed with future dementia, several possibilities could help explain our findings. It is thought that walking and cognition rely on similar brain regions, predominately in the prefrontal cortex . Gait is a complex process in which the locomotor systems receive input from the basal ganglia, motor cortex, and cerebellum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the mechanisms linking walking speed with future dementia, several possibilities could help explain our findings. It is thought that walking and cognition rely on similar brain regions, predominately in the prefrontal cortex . Gait is a complex process in which the locomotor systems receive input from the basal ganglia, motor cortex, and cerebellum .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that walking and cognition rely on similar brain regions, predominately in the prefrontal cortex . Gait is a complex process in which the locomotor systems receive input from the basal ganglia, motor cortex, and cerebellum . Although this process is largely automatic, walking relies on sensory feedback and high‐order cognitive control …”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevance of such a finding, gait slowing could not be considered as a specific parameter for either disease, as it also occurs in healthy aging. From a neuropathological point of view, gait slowing may be primarily due to neuropathological mechanisms that are common to normal aging and neurodegenerative diseases, especially increased prion-inflammatory makers and vascular burden (Valkanova and Ebmeier 2017). In the next sections, we identified dual-task-related changes in other parameters than gait speed that could be specific to AD and PD at the prodromal stage.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a recent meta-analysis including 14 studies, Bahureksa et al (2017) found that dual-task walking highlights the sensitivity of the latter gait parameters for discriminating between MCI subtypes and healthy controls. Furthermore, it has been shown that dual-taskrelated gait changes could differentiate between nonamnestic and amnestic MCI Valkanova and Ebmeier 2017). Specifically, the pace domain (i.e., gait speed and stride length) was more affected in non-amnestic MCI, whereas the rhythm (i.e., cadence, swing time, stance time, and double support time) and variability (i.e., stride length variability and swing time variability) domains were worse in amnestic MCI (Verghese et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews highlight the importance of measuring gait across the life course, from its development in children [47], link to fall risk [48,49] and its relationship to dementia in adults [50]. While clinically assessed gait speed has been shown to have use in assessing longevity and cognitive function in older adults [51,52], micro gait characteristics offer a more focused examination to differentiate pathology and identifying specific features of disease progression [53].…”
Section: Micro Gaitmentioning
confidence: 99%